A branched heterochronic pathway directs juvenile-to-adult transition through two LIN-29 isoforms - Chiara Azzi; Florian Aeschimann; Anca Neagu; Helge Großhans (eLife, 2020)
Robust organismal development relies on temporal coordination of disparate physiological processes. In Caenorhabditis elegans, the heterochronic pathway controls a timely juvenile-to-adult (J/A) transition. This regulatory cascade of conserved proteins and small RNAs culminates in accumulation of the transcription factor LIN-29, which triggers coordinated execution of transition events. We report that two LIN-29 isoforms fulfill distinct functions. Functional specialization is a consequence of distinct isoform expression patterns, not protein sequence, and we propose that distinct LIN-29 dose sensitivities of the individual J/A transition events help to ensure their temporal ordering. We demonstrate that unique isoform expression patterns are generated by the activities of LIN-41 for lin-29a, and of HBL-1 for lin-29b, whereas the RNA-binding protein LIN-28 coordinates LIN-29 isoform activity, in part by regulating both hbl-1 and lin-41. Our findings reveal that coordinated transition from juvenile to adult involves branching of a linear pathway to achieve timely control of multiple events.